Becoming a Macho Mensch: Stanley Kubrick, Spartacus and 1950s Jewish Masculinity. (30th March 2015) - Abrams, Nathan
Abstract : This article seeks to uncover the underlying Jewish thematics of Stanley Kubrick's Spartacus (1960). Explicit references to Jews, Jewishness, and Judaism were conspicuously absent from the film, but the Jewishness of Howard Fast's 1951 novel, combined with screenwriter Dalton Trumbo's various drafts, as well as the interventions of prime motivating force and star Kirk Douglas and Kubrick, still penetrated through to the final screen version, It focuses on three interrelated, yet wholly and previously unexplored, elements of the male Jewish self-image: the character of David the Jew, the Jewishness of the character Antoninus, and the Jewish philosophy of 'manliness' known as ' menschlikayt ', which privileged a Jewish posture of timidity, and denigrated as ' goyish ' or 'un/non-Jewish/Gentile', conventional masculinity. These I will deal with in turn, after having considered the role Kubrick actually played in making the film and what drew him to the material in the first place, before concluding with the importance of the Jewishness of Spartacus for understanding both Kubrick and his career as a whole. In so doing, it makes extensive use of archival materials in exploring the adaptation process.